Poliomyelitis and the “emergence” of rehabilitation in Argentina. A socio-historical analysis - Testa, Daniela Edelvis (2018)
The purpose of this article is to analyze ideas, definitions and practices linked to the “emergence” of rehabilitation in Argentina in the mid-20th century. Drawing on primary sources, we analyze conceptions about the medical and social problem of rehabilitating the “cripple,” and its presence on the public agenda between 1940 and 1960. Our results show that poliomyelitis epidemics were a significant factor in placing strain on the scope and contents of both social protection for people with disabilities and modernization projects related to rehabilitation, while forming the basis for subsequent developments in this field.